1994
DOI: 10.1557/proc-356-21
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Measurements of Stress-Controlled Interdiffusion in Multilayered Amorphous Alloys

Abstract: The decay of X-ray satellite intensities is used to measure interdiffusion in amorphous Ni 55 Zr 45 multilayers as a function of repeat distance, time and temperature. The data are compared to analytical expressions and a numerical simulation based on the analysis of Stephenson for stress effects. It is concluded that stress effects are very strong and that the analysis fits them quantitatively in a system such as a-Ni-Zr with marked diffusional asymmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…Studies on amorphous Ni-Zr multilayers 34,36,37,39,114 claim to have confirmed the predictions of the theory of Refs. 115 , and interpret the initial stages of fast interdiffusion not as subject to structural relaxation (cf.…”
Section: Diffusion-induced Stress Effects On Interdiffusion In Thesupporting
confidence: 73%
See 2 more Smart Citations
“…Studies on amorphous Ni-Zr multilayers 34,36,37,39,114 claim to have confirmed the predictions of the theory of Refs. 115 , and interpret the initial stages of fast interdiffusion not as subject to structural relaxation (cf.…”
Section: Diffusion-induced Stress Effects On Interdiffusion In Thesupporting
confidence: 73%
“…Several studies 34,36,37,39,114 claim a stress dependence of the (inter)diffusion coefficient in amorphous multilayers. These studies follow the theoretical treatment of Refs.…”
Section: Diffusion-induced Stress Effects On Interdiffusion In Thementioning
confidence: 99%
See 1 more Smart Citation
“…The Ni-Zr system is characterized by both strong miscibility and asymmetric diffusion of its components. Both these factors contribute to the rapid intermixing between Ni and Zr in multilayers and also to the build up of large stresses in this system due to unbalanced diffusional flow [22,23]. It has also been noted that the mechanical strength of these materials is related to this interdiffusional strain.…”
Section: Introductionmentioning
confidence: 99%